INKLUSI SOSIAL MELALUI JARINGAN KERJA GOTONG ROYONG PADA MASA PANDEMI - Leni Widi Mulyani (Fakultas Hukum Universitas Pasundan, 2020)
The Covid-19 pandemic has made the whole world experiences significant changes, including Indonesia. Public sectors were affected quite a bit, especially the economic sector for the middle to lower class. Community groups that depend on daily income have difficulty fulfilling their daily needs. Large-scale social restrictions (PSBB) on the one hand are unavoidable considering the many positive cases of Covid-19, in contrast many people facing difficulty to survive in the midst of economic uncertainty, this pandemic has a comprehensive social impact, economy and human rights, especially for vulnerable groups. The purpose of this research is to discuss social inclusion carried out by the community, especially in the Bandung area and its surroundings through mutual cooperation networks in overcoming the impact of the pandemic. The research method in this article uses normative legal research and uses a social approach method as well as a conceptual approach method, data collection techniques are taken through structured interview methods with social inclusion participants. The results of research in this paper are social inclusion and mutual cooperation between communities as a joint effort to reduce the impact of the Covid 19 pandemic. Real results have been felt by the poor and marginalized, not only in economy but also in learning about food security and independence. Keywords: Social inclusion, mutual cooperation, Covid-19.